Small Bowel Malignancy in Patient with Obscure Gastrointestinal Bleeding in Cipto Mangunkusumo Hospital, Diagnosed Using Double Balloon Enteroscopy: A Case Series - Hasan Maulahela; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Small bowel malignancy is still a rare case as a cause of gastrointestinal bleeding. The symptoms of small bowel malignancy are not specific.  One of the symptoms is obscure gastrointestinal bleeding.  Obscure gastrointestinal bleeding (OGIB) is defined as recurrent or persistent gastrointestinal bleeding when the result esophagogastroduodenoscopy and colonic endoscopy is negative. OGIB accounts for approximately 5% of all gastrointestinal bleeding events. Most OGIB events are attributable to small bowel disease. Double-balloon enteroscopy, also known as push-and-pull enteroscopy is an endoscopic technique for visualization of the small bowel. Here we present 5 cases of small bowel tumours in patient with obscure gastrointestinal bleeding who underwent double balloon enteroscopy at Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Three patients had confirmed gastrointestinal stromal tumour (GIST) from the histopathology examination, while 2 patients were diagnosed with adenocarcinoma.